Determinación de la rentabilidad, riesgos del cultivo y Comercialización de la sábila (Alloe vera L)N como alternativa productiva en la zona de Quinsaloma. - Súarez Vera, Leidy Silvana (2012)
The present work of investigation was realized in Quinsaloma's zone, province of The Rivers, during the period 2011-2012. His principal aim was to determine the production and commercialization of Sábila's culture, Aloe Side, in Quinsaloma's zone that understands nine areas: Los Cerritos, La Lorena, El Guabito, Las Palmitas, 12 de Octubre, Complejo Quinsaloma, Pambilar de Calope, Pambilar de Minuape y Magdalena de Chipe. For the production of the culture of sábila several processes realize the first term, the preparation of the area, preparation of you were, the chemical control of undergrowths in the epoch of pre-sowing and pre emergencies with 20 days before the sowing. Also the control of manual undergrowth, that this realized after sowing. The fertilization is programmed in agreement to the result of the analysis of the soil. It was necessary to apply a regulator of pH and fertilizer with - potassium nitrogens phosphorus, that Quinsaloma's soils lack these nutrients. A major fertilization is applied by organic matter as: Humus of Worm 35 %, guano of bull 35 %, poultry droppings 30 % these credits are applied with 20 days before transplant. A more key way of fertilizing in Quinsaloma's zone they are the dead coverages and green credits. The labors that are realized in the sowing, are the following ones, the pruning evil formation, the dug holes one all the areas, distancing of the sowing between rows and the density of sowing for hectare. Of equal way a phytosanitary control is kept to preserve the plant for his commercialization.